Recent developments on chitosan applications in regenerative medicine - Duarte, Ana Rita C. (2016)
Chitin is the second most abundant natural polymer, after cellulose, and it is mostly obtained from crustacean shells, such as crabs and/or shrimps [1]. It is, nonetheless, present in many other marine origin organisms, such as cephalopods. These alternative sources have recently started to gain more attention in order to obtain biopolymers with different characteristics [2].